Study of The Correlation Between Contact Angle Values with The Polarity of Liquids - Syahara, Muhammad Alwi; Kurniawan, Fredy; Anggriawan, Wahyu (IPTEK Journal of Proceedings Series, 2015)
Contact angle measurement is a technique which can be used to determine the surface properties of a substance and observe the interaction of surfaces. When polar liquid dropped on a non-polar solid, it will make an interaction that can observed from the contact angle. In simple way, the different polarity of the solid and the liquid sample will affect to the contact angle obtained. In this work the value of contact angle will be correlated to the polarity of the sample. The results showed that the plot between polarity parameter with contact angle on polytetrafluoroethylene substrat has a correlation which formed a sigmoidal curve with R2=0,954. It means the polarity of liquids can be determined by the contact angle values.